An iterative inter-track interference mitigation method for two-dimensional magnetic recording systems - C. Warisarn; T. Losuwan; P. Supnithi; P. Kovintavewat (My University, 2014)
At high recording density, the readback signal of two-dimensional magnetic recording is inevitably corrupted by the two-dimensional (2D) interference consisting of inter-symbol interference and inter-track interference (ITI), which can significantly degrade the overall system performance. This paper proposes an iterative ITI mitigation method using three modified 2D soft-output Viterbi algorithm (2D-SOVA) detectors in conjunction with an iterative processing technique to combat the 2D interference. The codeword of the outer code is divided and then written on three separate tracks. For every iteration, all 2D-SOVA detectors exchange the soft information to improve the reliability of the a priori information and use it in the branch metric calculation, before feeding the refined soft information to the outer decoder. Simulation results show that the proposed method outperforms the conventional receiver and the existing partial ITI mitigation method.
Keywords: Viterbi algorithm; Viterbi decoder; Cellular Automata and Applications